Analisis Komparatif Tentang Kriteria Kepala Negara Menurut Imam Al-Mawardi dan Imam Al-Ghazali - Nurdin, Safriadi; Marzuki Marzuki (Siyasah Wa Qanuniyah, 2023)
The Republic of Indonesia regulates the requirements for presidential and vice-presidential candidates in Law No. 7 of 2017, Article 169. This law is interesting to analyze from the perspective of whether it aligns with the qualifications outlined by Imam al-Mawardi in his work al-Ahkam as-Sulthaniyah and Imam al-Ghazali in al-Tibru al-Masbuk Fi Nashihati al-Muluk. These two scholars established criteria that a head of state must possess. This research uses a library research method with a descriptive qualitative approach. The results of the study show that, first, the criteria for a head of state according to Imam al-Mawardi consist of seven: (1) justice, (2) knowledge, (3) healthy senses, (4) healthy body, (5) a clear vision and mission, (6) courage and strength, (7) descent from the Quraysh. In contrast, the criteria for a head of state according to Imam al-Ghazali are ten, summarized into seven: (1) justice, (2) knowledge, (3) good religion and morals, (4) health, (5) trustworthiness, (6) receptive to the advice of scholars, (7) simplicity and closeness to the people. Second, the relevance of the ideas of Imam al-Mawardi and al-Ghazali concerning leadership requirements in Indonesia can be actualized and applied within the existing positive law in Indonesia, such as in the requirements for presidential and vice-presidential candidates as well as regional head candidates. The ideal leadership concepts from both scholars can serve as guidelines for leaders in Indonesia to implement in their leadership agenda.